Preoperative hemostasis and its association with bleeding and blood component transfusion requirements in cardiopulmonary bypass surgery. Issue 6 (31st August 2012) - Emeklibas, Nahit; Kammerer, Inna; Bach, Juergen; Sack, Falk‐Udo; Hellstern, Peter
<x xml:space="preserve">Abstract</x> BACKGROUND: Variables of hemostasis before surgery might indicate an elevated risk of bleeding. We determined hemostasis tests and standardized bleeding history and their association with bleeding and transfusion requirements in cardiopulmonary bypass (CPB) surgery. STUDY DESIGN AND METHODS: In a prospective trial, variables from 104 patients were associated with postsurgical bleeding and with red blood cells (RBCs) and platelet concentrate (PC) transfusions. Variables included standardized bleeding history, prothrombin time (PT), fibrinogen, fibrin monomers, Factor VIII, von Willebrand factor (VWF), multiple electrode aggregation (MEA), and the day of aspirin or thienopyridine withdrawal before operation. RESULTS: Multiple linear regression revealed bleeding history score, ADP‐induced MEA, CPB time, and hemoglobin (Hb) independently associated with postoperative bleeding and bleeding history, arachidonic acid (AA)‐induced MEA, CPB time, and PT associated with RBC transfusions. The logistic regression model for the outcome of bleeding within 24 hours after operation indicated ADP‐induced MEA, the day of aspirin withdrawal before operation, and CPB time as predictors. AA‐induced MEA, CPB time, Hb, and PT were predictors of RBCs transfusion. ADP‐induced MEA, the day of aspirin withdrawal, PT, and VWF were associated with PC transfusion. CONCLUSIONS: A standardized bleeding history may help to identify patients undergoing CPB surgery whose risk of bleeding is elevated. ADP‐induced MEA appears to predict postoperative bleeding and PC transfusion requirements, while AA‐induced MEA and preoperative Hb indicate the need for RBCs. The time of aspirin withdrawal before surgery influences perioperative blood loss and PC transfusion.